Constructability in industrial plants construction: a BIM-lean approach using the Digital Obeya Room framework - Nascimento, Daniel Luiz de Mattos; Sotelino, Elisa Dominguez; Lara, Thiago Pires Santoloni; Caiado, Rodrigo Goyannes Gusmão; Ivson, Paulo (Journal of Civil Engineering and Management, 2017)
One of the main problems the construction industry faces is the high cost and slow execution time due to inadequate planning, which results in poor use of human resources. A common solution for reducing time and costs is the adoption of prefabricated components (prefabs). This paper proposes a novel methodology for interdisciplinary management of construction projects by integrating Building Information Modeling (BIM) and Lean Thinking to improve the production planning and control of pipe-rack modules in an industrial facility. The article first presents a literature review to assess the key synergies between BIM and Lean Thinking. These led to the development of a new integrated work methodology named Digital Obeya Room. This model focuses on the required workflows, the analysis of collected data, and the visual management of construction planning and control. A real-world empirical study in the Oil and Gas industry evaluated how the newly devised practices could improve prefabrication and preassembly planning. The proposed methodology was capable of reducing the welding-time in 8.7% related on global prefabrication average in construction projects from Fails Management Institute (FMI) prefabrication report survey 2017.